The Analysis of Human Resources Policies and Regional Financial Accounting System on Regional Government Financial Statements’ Quality - Aida Nahar; Subadriyah Subadriyah; Ali Sofwan (Faculty of Economics, Universitas Sriwijaya, 2017)
Accountability of local governments in the implementation of policies should be carried out with the financial statements present the quality. Qualitative characteristics of financial statements described in PP 24/ 2005 that the qualitative characteristics of financial statements is a normative measurement that needs to be realized in the accounting information that can be fulfil its purpose. To be able to raise the normative requirements, this characteristics is absolutely necessary in order to meet the government 's financial statements desired qualities are: relevant, reliable, comparable, and understandable.The population of this research is PPK-SKPD in Karesidenan Pati. Consisting of: Regency Jepara, Kudus, Pati , Rembang, Blora, and Grobogan, totally 113 SKPD with 73 respondents with a random sampling technique . Data analysis technique used is multiple regression analysis. The results mentioned that human resource policies affect the quality of financial reporting by 4.167. Implementation of the system accounting effect on the quality of financial reporting by 3.309 % . Human resources policies and implementation of accounting systems affect the quality of financial statements. This study did not succeed accept hypothesis 5 proved that the value of t = -1.021 and p = 0.311, which means that the BPK audit does not affect the relationship between the Application System Accounting for the Quality of Regional Financial Statements.